Compassion in the Qur’an: A Study of Quraish Shihab’s Thought and its Implications for Learning in Islamic Education - Muhammad Nurfaizi Arya Rahardja; Udin Supriadi; Cucu Surahman (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study critically examines Quraish Shihab’s thoughts on the concept of compassion in the Qur’an, focusing on the meanings of four key terms: raḥmah, raḥmān, raḥīm, and ra’ūf. It employs a qualitative approach through a literature study that explores the theme of compassion in Quraish Shihab’s interpretations and its implications for learning within Islamic education. The data in this study are categorized into two types: primary data, consisting of verses related to compassion as interpreted in Tafsir al-Mishbah, and secondary data, which include scholarly articles, academic journals, books on Islamic education, and other relevant documents that support the theoretical and conceptual analysis of this research. Data collection was conducted through documentation methods, involving gathering written materials from both primary and secondary sources. The data analysis in this research comprises three stages: data reduction, data display, and conclusion drawing and verification. The findings of this study reveal that, according to Quraish Shihab, compassion in the Qur’an is represented through four terms: raḥmah, raḥmān, raḥīm, and ra’ūf. The implications of compassion from Quraish Shihab’s perspective for learning in Islamic education encompass four aspects: (1) the formation of humane and educational communication, (2) the provision of all learners’ needs, (3) perseverance in teaching that reflects raḥmāniyyah, and (4) a firm yet non-authoritarian attitude.